Sensing of joint and spinal bending or stretching via a retractable and wearable badge reel - Li, Chengyu; Liu, Di; Xu, Chaoqun; Wang, Ziming; Shu, Sheng; Sun, Zhuoran; Tang, Wei; Wang, Zhong Lin (Nature communications, 2021)
Human motions, such as joint/spinal bending or stretching, often contain information that is useful for orthopedic/neural disease diagnosis, rehabilitation, and prevention. Here, we show a badge-reel-like stretch sensing device with a grating-structured triboelectric nanogenerator exhibiting a stretching sensitivity of 8 V mm −1 , a minimum resolution of 0.6 mm, a low hysteresis, and a high durability (over 120 thousand cycles). Experimental and theoretical investigations are performed to define the key features of the device. Studies from human natural daily activities and exercise demonstrate the functionality of the sensor for real-time recording of knee/arm bending, neck/waist twisting, and so on. We also used the device in a spinal laboratory, monitoring human subjects’ spine motions, and validated the measurements using the commercial inclinometer and hunchback instrument. We anticipate that the lightweight, precise and durable stretch sensor applied to spinal monitoring could help mitigate the risk of long-term abnormal postural habits induced diseases. Human motions often contain information that is useful for orthopedic/neural disease diagnosis, rehabilitation, and prevention. Here, the authors show a badge-reel-like stretch sensing device with a grating-structured triboelectric nanogenerator for joints/spine bending or stretching sensing.